2017
DOI: 10.1504/wremsd.2017.10003436
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial education and internationalisation of firms in transition economies: a conceptual framework from the case of Croatia

Abstract: The aim of this paper is to offer an integrated perspective on internationalisation process in transition economies and the role that an entrepreneurial education can play in it. The context of a transition economy, such those countries belonging to the former Yugoslavian republic, deeply affect the entrepreneurial activities established. Internationalisation offers a viable advantage to entrepreneurs and their firms to overcome a limited internal market and hostile conditions faced in the local environment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 121 publications
(184 reference statements)
0
2
0
1
Order By: Relevance
“…According to the theory of role identification [70], social networks can initiate an imitative behaviour [71]. A study dedicated to transition countries, especially Croatia, concluded that personal networks and relational strategy help to overcome blockages in entrepreneurship activity, and they are the main solution for recognizing opportunities for access to resources in the desired quantity and quality, to capital, and knowledge [72].…”
Section: Networkingmentioning
confidence: 99%
“…According to the theory of role identification [70], social networks can initiate an imitative behaviour [71]. A study dedicated to transition countries, especially Croatia, concluded that personal networks and relational strategy help to overcome blockages in entrepreneurship activity, and they are the main solution for recognizing opportunities for access to resources in the desired quantity and quality, to capital, and knowledge [72].…”
Section: Networkingmentioning
confidence: 99%
“…Por consiguiente, la academia debe convertirse en el axioma que facilite los procesos de internacionalización de las economías en los nuevos mercados, especialmente aportar a los emprendimientos mediante el fortalecimiento de las redes de interés (Dabic, Caputo, Rialti & Pellegrini, 2017). De ahí que la académica apropie desde una concepción holística sus procesos de internacionalización para diversificar tanto sus fuentes de financiación como las capacidades de los graduados en el campo empresarial (Minola, Donina & Meoli, 2016).…”
Section: Subárea 2: Educación En La Internacionalización De Los Empreunclassified
“…Given emerging economies, these firms are more susceptible to fast, turbulent environmental changes (Altinay et al, 2021; Marquis & Raynard, 2015). These firms often face serious impediments such as the ability to identify opportunities (Gorodnichenko & Schnitzer, 2013), find required capital (Rialti et al, 2017) and most of the time, lack of precise information (Misbauddin & Nabi, 2019). To navigate the ever‐changing environment, SMEs rely highly on intricate networks within service ecosystems.…”
Section: Introductionmentioning
confidence: 99%